2013
DOI: 10.3892/or.2013.2723
|View full text |Cite
|
Sign up to set email alerts
|

Forced downregulation of RACK1 inhibits glioma development by suppressing Src/Akt signaling activity

Abstract: Abstract. Glioma is the most common primary brain malignant tumor. Receptor for activated C-kinase 1 (RACK1) is widely expressed in the central nervous system, and regulates multiple cellular processes including cell survival, proliferation, migration and metastasis. However, the role of RACK1 in glioma has never been revealed. The present study, for the first time, showed that RACK1 expression was significantly higher in glioma tissues and cell lines when compared with that in normal brain tissues, and was po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…AKT is considered as an important key protein regulating tumor progression in various types of human cancer. Peng et al showed knocking down RACK1 in vitro decreased AKT activity in glioma (37). We further investigated whether RACK1 expression and AKT activation are relevant in human OSCC cell lines and clinical samples.…”
Section: Rack1 Silencing Induces G1 and G2 Phase Cell Cycle Arrestmentioning
confidence: 93%
“…AKT is considered as an important key protein regulating tumor progression in various types of human cancer. Peng et al showed knocking down RACK1 in vitro decreased AKT activity in glioma (37). We further investigated whether RACK1 expression and AKT activation are relevant in human OSCC cell lines and clinical samples.…”
Section: Rack1 Silencing Induces G1 and G2 Phase Cell Cycle Arrestmentioning
confidence: 93%
“…Bcl-2 is a potent suppressor of cell apoptosis, 46 while Bax is a proapoptotic member of the Bcl-2 protein family; overexpression of Bax indicates an apoptosis-inducing tendency. 47 Regardless of whether an extrinsic or intrinsic apoptotic pathway is activated, caspase-3 is always activated downstream of apoptotic pathways 48 and plays an important role in cell death.…”
Section: Effects Of Phase and Topography Of Tio 2 Nanotubes On Cell Amentioning
confidence: 99%
“…RACK1 expression varies in different cancer types (13). It is up-regulated in most cancer types, such as hepatocellular carcinoma (35,36), non-small-cell lung cancer (37), and glioma (38), but decreased in gastric cancer (17). Deregulation of Wnt signaling has been observed in multiple tumors, especially in colon cancer, and we have reported that Dvl expression is negatively correlated with autophagy in the late stage of colon cancer development (10).…”
Section: Discussionmentioning
confidence: 82%